Biological Activities of Aqueous Extracts from Marine Sponges and Cytotoxic Effects of 3-Alkylpyridinium Polymers from Reniera sarai - Sepčić, K.; Batista, U.; Vacelet, J.; Maček, P.; Turk, T. (Comparative Biochemistry and Physiology Part C: Pharmacology, Toxicology and Endocrinology, 1997)
We screened the biological activity of 21 marine sponges collected in the northern Adriatic sea. Hemolytic, hemagglutinating, antimicrobial, cytotoxic, and anti-acetilcholinesterase activities of the extracts were monitored. We found that hemolytic activity was generally weak; only extracts from three sponge species possess considerable activity. Hemagglutinating activity was present in almost half of extracts but with little specificity against human erythrocytes of different blood groups. Detectable antimicrobial activity was present in only two extracts, while most of them possessed cytotoxic activity. Strong anti-cholinesterase activity was present only in one sample. 3-alkypyridinium polymers isolated from Reniera sarai were hemolytic and strongly cytotoxic against different cell lines with slightly expressed specificity against transformed cells.